Broad spectrum immunomodulation using biomimetic blood cell margination for sepsis therapy. Issue 4 (15th January 2016) - Hou, Han Wei; Wu, Lidan; Amador-Munoz, Diana P.; Vera, Miguel Pinilla; Coronata, Anna; Englert, Joshua A.; Levy, Bruce D.; Baron, Rebecca M.; Han, Jongyoon
Abstract : A novel microfluidics approach for broad spectrum removal of pathogens, leukocytes and cytokines based on biomimetic cell margination. Abstract : Sepsis represents a systemic inflammatory response caused by microbial infection in blood. Herein, we present a novel comprehensive approach to mitigate inflammatory responses through broad spectrum removal of pathogens, leukocytes and cytokines based on biomimetic cell margination. Using a murine model of polymicrobial sepsis induced by cecal ligation and puncture (CLP), we performed extracorporeal blood filtration with the developed microfluidic blood margination (μBM) device. Circulating bacteremia, leukocytes and cytokines in blood decreased post-filtration and significant attenuation of immune cell and cytokine responses were observed 3–5 days after intervention, indicating successful long-term immunomodulation. A dose-dependent effect on long-term immune cell count was also achieved by varying filtration time. As proof of concept for human therapy, the μBM device was scaled up to achieve ∼100-fold higher throughput (∼150 mL h −1 ). With further multiplexing, the μBM technique could be applied in clinical settings as an adjunctive treatment for sepsis and other inflammatory diseases.